A Study of the Apology Strategies Used by Iraqi EFL University Students - Raed Latif Ugla; Mohamad Jafre Zainol Abidin (International Journal of Evaluation and Research in Education (IJERE), 2016)
This study was aimed at exploring apology strategies of English used by Iraqi EFL students, apology strategies in Iraqi Arabic and the pragmatic strategies of Iraqi EFL students in relation to the use of apology as a speech act. The data analyzed in this study were collected in Al-Yarmouk University College and University of Diyala. The study was mixed method in nature using a questionnaire and an interview adapted from previous studies. The quantitative data was obtained from fifty-five Iraqi EFL students using Discourse Completion Task Questionnaires (DCTQ) while the qualitative data obtained from individual interviews carried out with twelve Iraqi EFL students. The results were showed different kinds of apology strategies used by Iraqi EFL students. A new classification of apology strategies was provided in this study. Results of the study showed that Iraqi EFL students used a variation of apology strategies, they were well aware of how to use adequate apology forms to meet the requirements of specific situations and relationships, and they felt the need for explaining and avoiding interpretation of their response as an apology.